2022
DOI: 10.31222/osf.io/dzych
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can Confirmation Bias Improve Group Learning?

Abstract: Confirmation bias has been widely studied for its role in failures of reasoning. Individuals exhibiting confirmation bias fail to engage with information that contradicts their current beliefs, and, as a result, can fail to abandon inaccurate beliefs. But although most investigations of confirmation bias focus on individual learning, human knowledge is typically developed within a social structure. How does the presence of confirmation bias influence learning and the development of consensus within a group?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Our study suggests there is a similar mechanism at play with CARL, at least in fully-connected networks. In the social case, similar results have been obtained by Gabriel & O'Connor with an opiniondynamics model [20], and independently from resource scarcity. The authors argue that a moderate confirmation bias actually serves group learning, and could have developed in the social environment in which humans evolved.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our study suggests there is a similar mechanism at play with CARL, at least in fully-connected networks. In the social case, similar results have been obtained by Gabriel & O'Connor with an opiniondynamics model [20], and independently from resource scarcity. The authors argue that a moderate confirmation bias actually serves group learning, and could have developed in the social environment in which humans evolved.…”
Section: Discussionsupporting
confidence: 82%
“…But it was not obvious that a confirmation bias would also lead to poorer performance in groups of two or three agents. Similar results, however, have been obtained by Gabriel & O'Connor with an opinion-dynamics model, and independently from resource scarcity [20]. The authors implemented a "strong confirmation bias", and showed that, for small group sizes, strongest biases harm correct consensus.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The impact of confirmation bias in groups on group learning and performance remains an open question since we investigated confirmation bias and learning in two different experimental paradigms. It has been suggested that moderate confirmation bias may enhance individual 35 and group performance 36 when learning, and that intermittent social information improves collective problem-solving 37 . Understanding the conditions under which group decisions and associated confirmation biases contribute to accuracy and learning is an important avenue for future research on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…It may seem obvious that in-group bias should create divisions between groups, inhibiting consensus formation. However, in-group bias may also speed up the convergence of opinions within in-groups, thus allowing opinions to spread further across the network before polarization can take hold [ 50 , 51 ]. This suggests that the structure of social interactions may moderate the effects of in-group bias.…”
Section: Introductionmentioning
confidence: 99%